Task-independent acute effects of delta-9-tetrahydrocannabinol on human brain function and its relationship with cannabinoid receptor gene expression: A neuroimaging meta-regression analysis. (September 2022) - Gunasekera, Brandon; Davies, Cathy; Blest-Hopley, Grace; Veronese, Mattia; Ramsey, Nick F.; Bossong, Matthijs G.; Radua, Joaquim; Bhattacharyya, Sagnik; ,; Pretzsch, Charlotte; McAlonan, Gráinne; Walter, Carmen; et al.
Abstract: The neurobiological mechanisms underlying the effects of delta-9-tetrahydrocannabinol (THC) remain unclear. Here, we examined the spatial acute effect of THC on human regional brain activation or blood flow (hereafter called 'activation signal') in a 'core' network of brain regions from 372 participants, tested using a within-subject repeated measures design under experimental conditions. We also investigated whether the neuromodulatory effects of THC are related to the local expression of the cannabinoid-type-1 (CB1R) and type-2 (CB2R) receptors. Finally, we investigated the dose-response relationship between THC and key brain substrates. These meta-analytic findings shed new light on the localisation of the effects of THC in the human brain, suggesting that THC has neuromodulatory effects in regions central to many cognitive tasks and processes, related to dose, with greater effects in regions with higher levels of CB1R expression. Highlights: Augmented activation signal, by THC relative to placebo, in key brain regions. A direct relationship between brain signal change by THC and CB1R expression. A dose-response relationship was observed with THC dose in certain brain regions.